PENCEGAHAN STUNTING MELALUI SOSIALISASI PROGRAM BAPAK ASUH ANAK STUNTING DI KABUPATEN SUBANG - Willya Achmad; Rizky Ilhami (Sean Institute, 2022)
Stunting is a chronic nutritional problem that stunts children's physical growth and cognitive development, having a long-term impact on their future health and productivity. This study aims to investigate the effectiveness of the socialization of the Bapak Asuh Anak Stunting (BAAS) program in stunting prevention efforts in Subang Regency, Indonesia. This study utilized a qualitative design. Data was collected through a structured survey of mothers of children under five and fathers in Subang District. The results showed that the